Masalah Peserta Didik Unpopular Berdasarkan Hasil Sosiometri Kelas XI di SMA N 2 Bayang Kabupaten Pesisir Selatan - Febriani, Rati; Ibrahim, Indra; Wira Nita, Rahma (Bimbingan dan Konseling, 2013)
The problem in this research is the problem of students based on the results of sociometry unpopular class XI in SMA N 2 Bayang Kabupaten Pesisir Selatan of the issue of personal views of the lack of discipline, still childish, self esteem, lack of confidence to the class, the social problems seen from stiff in the mix, enjoys less criticism of others, less socializing in the classroom, lack of self-control and irritable, interact with friends in class. The purpose of this study was to: (1) describe the personal problems of learners unpopular based on sociometry (2) describe the social problems of students based on the results of sociometry unpopular. This research is a descriptive study. The population in this study was based on the results of learnerâs unpopular sociometry XI classes totaling 50 people. This study uses total sampling. So the total sample of 50 people. The instrument used in this study was a questionnaire. While the percentage of use data analysis techniques. Based on the research findings recommended: (1) counselor and parents to equally provide support and cooperation in order to assist and provide guidance to students unpopular in the face of his problems (2) Department of Education Painan Pesisir Selatan to consider issues learners in order to resolved unpopular and work together with BK teachers so that it can good social relations at school and objectives can be achieved optimally education.